2013
DOI: 10.1111/jog.12032
|View full text |Cite
|
Sign up to set email alerts
|

p.His165Pro: A novel SOX9 missense mutation of campomelic dysplasia

Abstract: Campomelic dysplasia (CD) is a rare skeletal dysplasia caused by mutation in the SOX9 gene located on chromosome 17q24.3-q25.1, which regulates testis and chondrocyte development. Severe bowing of the long bones was seen at second-trimester scan. DNA analysis demonstrated a previously unreported de novo missense mutation in p.His165Pro. Ultrasound-based, molecular biology diagnosis led to early therapeutic termination of pregnancy. Histologic examination of the femoral epyphyseal growth plate confirmed scanty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Understanding the underlying molecular etiologies was very helpful in classification of specific types of genetic skeletal disorders. The newly discovered mutations in previous literatures and our study have greatly enriched the mutation spectrum of SD, 41–45 which benefit to the genetic diagnosis and consultation of this disease.…”
Section: Discussionmentioning
confidence: 70%
“…Understanding the underlying molecular etiologies was very helpful in classification of specific types of genetic skeletal disorders. The newly discovered mutations in previous literatures and our study have greatly enriched the mutation spectrum of SD, 41–45 which benefit to the genetic diagnosis and consultation of this disease.…”
Section: Discussionmentioning
confidence: 70%
“…Since changes in SOX9 associated with CD are mainly private mutations, the alterations identified here expand the spectrum of SOX9 pathogenic variations to about seventy ( Table S3 ) ( Thong et al , 2000 ; Giordano et al , 2001 ; Preiss et al , 2001 ; Sock et al , 2003 ; Michel-Calemard et al , 2004 ; Hsiao et al , 2006 ; Shotelersuk et al , 2006 ; Beaulieu et al , 2009 ; Gentilin et al , 2010 ; Okamoto et al , 2010 ; Staffler et al , 2010 ; Kim et al , 2011 ; Stoeva et al , 2011 ; Chen et al , 2012 ; Gopakumar et al , 2013 ; Matsushita et al , 2013 ; Tonni et al , 2013 ). Premature termination codons (PTCs) are the most prevalent mutational class in CD, accounting for approximately 45% of all the alterations identified.…”
Section: Discussionmentioning
confidence: 84%
“…Commonly, prenatal diagnosis of CD is made in the second trimester of pregnancy: Promsonthi and Wattanasirichaigoon (2006) reported a 3D ultrasound diagnosis made at 26 weeks' gestation and emphasized the advantages of the surface-rendering mode of 3D ultrasound in evaluating fetal skeletal dysplasia; Gentilin et al (2010) described five cases prenatally detected between 12 and 32 weeks in which the diagnosis was confirmed by molecular analysis of SOX9 gene; Tonni et al (2013) reported a previously unreported de novo missense mutation in p.His165Pro in a fetus with severe bowing of the long bones, cystic hygroma, Pierre Robin sequence, bilateral hydronephrosis and ascites. Massardier et al (2008) reported two cases suspected at the 13 th week and presented with hygroma colli along with anomalies in the lower but not the upper limbs: when first trimester hygroma colli is accompanied by specific findings of the lower limbs, the diagnosis of CD can be investigated through SOX9 mutation analysis.…”
mentioning
confidence: 99%